Factors contributing to the vulnerability of healthcare providers in the Bandundu Health Zone and their impact on the ineffectiveness of epidemiological surveillance within the One Health approach - Manta, S. L.; Ngwamah, A. F. B.; Koto-Te-Nyiwa Ngbolua, Jean-Paul; Mawunu, M.; Mukandu, B. B. L.; Ntoto, B. N. (Orapuh Journal, 2025)
IntroductionThe One Health approach highlights the interconnectedness of human, animal, plant, and ecosystem health. Approximately two-thirds of human infectious diseases are zoonotic, with many emerging diseases linked to wildlife. Effective surveillance under the One Health approach is critical for preventing and managing these diseases.PurposeThis study aimed to assess the factors influencing non-compliance with surveillance standards under the One Health approach in the Bandundu Health Zone, focusing on healthcare providers' knowledge, training, and stakeholder involvement.MethodologyA cross-sectional analytical study was conducted through field surveys with 200 healthcare providers using a structured questionnaire. Systematic probability sampling was applied to ensure representativeness.ResultsAmong the 200 respondents, 62.5% were women, 56.5% were aged 26–33 years, and 70% were nurses with 6 to 10 years of experience. The key findings of the study showed that 80% lacked adequate knowledge of the One Health approach, and 63% were unaware of zoonotic diseases. Education level was found to significantly influence non-compliance with surveillance standards (χ² = 32.2, dof = 1, p = 0.00). Additionally, there were significant gaps in training on the One Health approach (χ² = 37.1, dof = 1, p = 0.00), with 94% of respondents reporting insufficient stakeholder involvement and 78% failing to comply with surveillance standards. Statistically significant associations were observed between knowledge of surveillance functions (χ² = 12.8, dof = 1, p = 0.00) and the failure to involve veterinarians and agronomists in the process (χ² = 17.9, dof = 1, p = 0.00).ConclusionThis study identified critical barriers to effective epidemiological surveillance under the One Health approach, including insufficient knowledge, inadequate training, and limited stakeholder engagement. To address these challenges, capacity-building and targeted training programs are essential for improving surveillance practices. Cross-disciplinary collaboration, particularly the inclusion of veterinary and agronomic expertise, is vital for enhancing compliance with One Health standards. Public health policies should prioritize these interventions to strengthen surveillance systems, improve zoonotic disease monitoring, and ultimately safeguard public health.